Towards a smart object network for clinical services. - Sedlmayr, Martin; Becker, Andreas; Münch, Ulli; Meier, Fritz; Prokosch, Hans-Ulrich; Ganslandt, Thomas (Annual Symposium proceedings, 2009)
Radio Frequency Identification (RFID) technology has become prevalent in logistics to support and optimize processes and numerous projects investigate its opportunities and challenges in the clinical context. However, most approaches are focused on one specific application using only a few possibilities of the technology. We describe the development of a smart object network to serve as a generic platform for various clinical services. Based on two disparate scenarios - tracking medical devices and transfusion safety - the architecture, implementation issues and prospects of such a platform are discussed.
CRIS-Team Scopus Importer:2021-11-16